Answer:
-16b+40b^2
Step-by-step explanation:
-8b*2=-16b
(-8b)(-5b)=40b^2
Answer:
![\boxed{=-23}](https://tex.z-dn.net/?f=%5Cboxed%7B%3D-23%7D)
Explanation: You had to used pemdas stands for: p-parenthesis, e-exponents, m-multiply, d-divide, a-add, and s-subtracting that came from left to right.
First you had to multiply and divide from left to right.
![24/(-3)=-8(2)](https://tex.z-dn.net/?f=24%2F%28-3%29%3D-8%282%29)
![8*2=16](https://tex.z-dn.net/?f=8%2A2%3D16)
![-7-16](https://tex.z-dn.net/?f=-7-16)
Then you add and subtract from left to right.
![-7-16=-23](https://tex.z-dn.net/?f=-7-16%3D-23)
![=-23](https://tex.z-dn.net/?f=%3D-23)
Final answer: ![\boxed{=-23}](https://tex.z-dn.net/?f=%5Cboxed%7B%3D-23%7D)
Hope this helps!
And thank you for posting your question at here on brainly, and have a great day.
-Charlie
we are given that
3 chickens to lay 32 eggs
now, we can find number of eggs per chicken
number of eggs per chicken= (total eggs)/(total chicken)
so, we get
number of eggs per chicken is
![=\frac{32}{3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%7D%7B3%7D)
now, we can set up following
1.5 chicken : 1.5 eggs : 1.5 days
3 chickens : 3 eggs : 1.5 days
1 chicken : 1 egg : 1.5 days
Since, changing number of chicken won't affect time
time to lay eggs will always remain same
so,
for 1 chicken to lay
eggs
it takes
![=\frac{32}{3}*1.5 days](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%7D%7B3%7D%2A1.5%20days)
..............Answer
Answer:
4
Step-by-step explanation:
Brackets always mean "DO THIS FIRST!!!"
2+6 = 8
Then, do 3 x 8. That is 24.
24 divided by 4 is 6.
6 - 2 is 4!
F(5) is equal to 17.
f(5)= 3(5)+2= 17